Best Practices for Allocating Appropriate Credit and Responsibility to Authors of Multi-Authored Articles - Eggert, Lucas D. (Frontiers in Psychology, 2011)
Today’s research process is characterized by multidisciplinary research projects. This situation inevitably leads to the question on how to decide on who will be an author of a multi-authored publication. This question becomes even more important as scientists must stand up for their own interest because of the ever-increasing importance of individual scientists’ publication records. At worst, discussions about authorship allocation might lead to a serious conflict among coworkers that might even endanger the successful completion of a whole research project. Surprisingly, ethical standards on authorship are apparently not discussed in the field of Cognitive Science. In this short review I therefore characterize the modern challenges to a fair system for allocating authorship and review existing standards to compile a list of best practice principles and recommendations for determining authors in multi-authored publications.